VD_FINDINFO HC / 2021 / 36 vom 12. Februar 2021 - VD Tribunal cantonal (2021)
OBLIGATION D'ENTRETIEN, PROTECTION DE L'UNION CONJUGALE, GARDE ALTERNÉE | 176 al. 1 ch. 1 CC, 176 al. 3 CC, 276 CC, 285 CC, 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH)